THE TRANSLATION OF THESIS ABSTRACTS IN THE ACCOUNTING DEPARTMENT OF BRAWIJAYA UNIVERSITY - Esti Junining, M.Pd. (ISSN)
As many errors were found in the translation of thesis abstracts in the Accounting Department of Brawijaya University, the study was conducted to see (1) the kinds of linguistic errors that exist in the translation of the S-1 thesis abstracts of the Accounting Department, and (2) the degree of informativeness in the translation of thesis abstracts. This study was designed by descriptive qualitative research, which intended to describe the fifteen pieces of abstracts taken from five pieces in each batch ranging from the academic year of 2000 to 2002, and then the data were analyzed using content analysis. The result of the study shows that the kinds of linguistic errors are grammatical errors (78%), followed by lexical errors (22%) successively. Although there are more than seventy five percent errors occurred, the translation of the abstracts was still considered positively informative.